Hungarian Monitoring, 15 April 1990 . [Magyar rádiófigyelő], 1990. április 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Congress of the Mongolian Communist Party - Easter in East Europe Domestic Affairs: - Coalition talks between the Hungarian Democratic Forum (MDF) and Independent Smallholders, Agrarian Workers and Civic Party (FKGP) - Military helicopters over Hungarian towns in Transylvania - Soviet Ambassador to Hungary has left the country - The Democratic Alliance of Hungarians in Romania published its statutes Külpolitika: - A mongol kommunista párt kongresszusa - Húsvét Kelet-Európában Belpolitika: - MDF-FKGP koalíciós tárgyalások - Katonai helikopterek erdélyi magyar városok felett - A szovjet nagykövet elhagyja az országot - Az RMDSZ nyilvánosságra hozza alapszabályait